Optical and electrical properties of undoped and doped Ge nanocrystals - Das, Samaresh (Springer, 2012)
Size-dependent photoluminescence characteristics from Ge nanocrystals embedded in different oxide matrices have been studied to demonstrate the light emission in the visible wavelength from quantum-confined charge carriers. On the other hand, the energy transfer mechanism between Er ions and Ge nanocrystals has been exploited to exhibit the emission in the optical fiber communication wavelength range. A broad visible electroluminescence, attributed to electron hole recombination of injected carriers in Ge nanocrystals, has been achieved. Nonvolatile flash-memory devices using Ge nanocrystal floating gates with different tunneling oxides including SiO(2), Al(2)O(3), HfO(2), and variable oxide thickness [VARIOT] tunnel barrier have been fabricated. An improved charge storage characteristic with enhanced retention time has been achieved for the devices using VARIOT oxide floating gate.